The Impact of Enforcement of Corruption Law by the Corruption Eradication Commission after the Ratification of the Latest KPK Law - Ayu Putriyana; Nur Rochaeti (Jurnal Penelitian Hukum De Jure, 2021)
2019 was a year full of turmoil for the KPK (Corruption Eradication Commission) due to the revision of the KPK Law after 17 years of the KPK Law being in effect. Despite many rejections, the latest KPK Law was still passed in September 2019 so that it became Indonesia's positive law. Therefore, the statements of the problem in this research are: what is the cause of the KPK Law revision and what is the impact of law enforcement on corruption by the KPK after the ratification of the latest KPK Law. The purpose of this research is to find out the reasons for the revision of the KPK Law and the impact of the implementation of the latest KPK Law. The method used in this research is a normative juridical method with a descriptive qualitative approach. The results of the research indicate that there are several weaknesses of the previous KPK Law which have an impact on the performance of the KPK so that it has not provided maximum results. In fact, regarding the impact of the enactment of the latest KPK Law, it has not given positive results so that it affects the stability of law enforcement for corruption. Therefore, there needs to be a good adaptation for the KPK and all related parties so that the latest KPK Law can run well.